Effectiveness of Leaflet Media on PHBS Knowledge and Attitudes in The Elderly and Pre-Elderly in Jogokariyan Village - Muhammad Jamalludin; Dwiki Bagaskara; Aprillia Krisnawaty; Putriayu Nurdianti; Rochana Ruliyandari (Sean Institute, 2025)
PHBS (Clean and Healthy Living Behavior) involves conscious actions by individuals, families, and communities to maintain health and prevent disease. Increasing awareness and attitudes toward PHBS can be achieved through health education programs, including the use of leaflets to enhance knowledge and attitudes among the elderly and pre-elderly. This study aims to increase awareness and understanding of the elderly and pre-elderly about PHBS in Jogokariyan Village RW 10. This quasi-experimental study used a one-group pretest-posttest design in Jogokariyan Village RW 10 (February 2025). The population included all elderly and pre-elderly residents, with 27 respondents selected through purposive sampling. Data were analyzed using univariate and bivariate methods, including paired sample t-tests. The average attitude score increased from 30.56 in the pretest to 32.07 in the posttest, showing a difference of 1.51. Univariate analysis showed that after PHBS education using leaflet media, 70.4% of households showed good to very good knowledge compared to the pre-education level.Likewise, the percentage of households that have a positive attitude towards PHBS increased from 40.7% to 63.0% after receiving leaflet-based education. The results of the paired t-test on the knowledge variable obtained a p value of 0.000 (> 0.05) and an attitude of 0.002 (> 0.05). This shows that there is a significant difference between knowledge and attitudes before and after health education using leaflet media. This shows a significant relationship between attitudes, knowledge and PHBS education of the elderly and pre-elderly using leaflet media. Based on the results of counseling activities using leaflet media, it can be concluded that the use of this educational media has proven effective in increasing knowledge and attitudes about Clean and Healthy Living Behavior in the elderly and pre-elderly in Jogokariyan Village.